PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH DASAR: STUDI KUALITATIF - Besse Marhawati (Universitas Negeri Malang, 2020)
Abstract: This study aims to describe the implementation of the academic supervision of the Principal of State Elementary School 2 Telaga Gorontalo Regency. The approach used is a qualitative approach with a case study design. Data collection is done through: in-depth interviews, observation, and documentation. Data were analyzed by steps: data reduction, data presentation, drawing conclusions. The results showed that the implementation of primary school principal’s academic supervision included: (1) the efforts of principals to achieve achievements, namely: guiding and encouraging teachers and students in academic and non-academic activities, and providing supporting facilities and infrastructure in achieving academic and non-academic achievements; (2) the principal’s academic supervision program, namely: group supervision and individual supervision; (3) the strategy of implementing school principal academic supervision namely: implementing group supervision through Teacher Working Group (Kelompok Kerja Guru / KKG) activities and individual supervision through scheduled supervision activities in odd / even semester and clinical supervision (teacher’s own request as needed); and (4) supporting factors in the implementation of school principals’ academic supervision, namely: there is high concern from the headmaster in conducting supervision, there is high motivation from teachers in conducting supervision, and there is adequate infrastructure and support in the implementation of supervision. Keywords: academic supervision, principal, elementary school Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan supervisi akademik Kepala Sekolah Dasar Negeri 2 Telaga Kabupaten Gorontalo. Pendekatan yang digunakan adalah pendekatan kualitatif dengan rancangan studi kasus. Pengumpulan data dilakukan melalui: wawancara mendalam, observasi, dan dokumentasi. Data dianalisis dengan langkah-langkah: reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pelaksanaan supervisi akademik kepala sekolah dasar meliputi: (1) upaya kepala sekolah mencapai prestasi yaitu: membimbing dan mendorong guru dan siswa dalam kegiatan akademik dan nonakademik, dan menyediakan sarana dan prasarana pendukung dalam pencapaian prestasi akademik dan nonakademik; (2) program supervisi akademik kepala sekolah yaitu: supervisi kelompok dan supervisi individual; (3) strategi pelaksanaan supervisi akademik kepala sekolah yaitu: pelaksanaan supervisi kelompok melalui kegiatan Kelompok Kerja Guru (KKG) dan supervisi individual melalui kegiatan supervisi yang terjadwal pada semester gasal / genap dan supervisi klinis (permintaan guru sendiri sesuai kebutuhan); dan (4) faktor pendukung dalam pelaksanaan supervisi akademik kepala sekolah yaitu: adanya kepedulian yang tinggi dari kepala sekolah dalam pelaksanaan supervisi, adanya motivasi yang tinggi dari guru dalam pelaksanaan supervisi, dan adanya dukungan sarana dan prasarana yang memadai dalam pelaksanaan supervisi. Kata kunci: